Literature Review: Implementation of Local Area Network (LAN) Using Star Topology in Educational Environments - Fatma Aji Margi Lestari; Noufal Afif Nur Fadillah Ali (MIKIR : Mathematics, Informatics, Knowledge And Information Research, 2026)
Local Area Network (LAN) is one of the most widely implemented information technology infrastructures within limited geographic areas such as office buildings, campuses, and educational institutions. This literature review aims to build a comprehensive framework regarding LAN implementation by reviewing, summarizing, and critically analyzing previous relevant studies. The method used is a systematic literature study by collecting trusted sources including peer-reviewed journals, books, and technical reports published within the last three years. The results indicate that the success of LAN implementation is greatly influenced by the appropriate selection of topology, hardware quality, protocol configuration, and the implementation of comprehensive network security systems. Furthermore, advances in Wireless LAN technology and Software-Defined Networking (SDN) open new opportunities for more flexible and efficient network management. This review also examines aspects of planning, testing, maintenance, and real-world challenges encountered in LAN implementation across various organizational environments. This review concludes that well-planned LAN implementation has been proven to enhance productivity, data communication efficiency, and information security across various organizational environments, while serving as a foundation for sustainable digital transformation.